Design and generation of a glutaminase GLS2 conditional knockout mice - Peñalver, Ana; Tosina, Marta; Martín-Rufián, Mercedes; Campos-Sandoval, José Ángel; Alonso-Carrión, Francisco José; Segura-Checa, Juan Antonio; Mates-Sánchez, José Manuel; Ramírez, Miguel Ángel; Gutiérrez-Adán, Alfonso; Márquez-Gómez, Javier (My University, 2014)
Mammalian glutaminase (GA; EC 3.5.1.2) is the main enzyme involved in brain generation of glutamate (Glu). This amino acid acts as an excitatory neurotransmitter within the CNS, and it is also implicated in behavioral sensitization through the mesolimbic pathway. Two different GA genes have been described: Gls that encodes the isozymes KGA and GAC, and Gls2, which encodes GAB and LGA isozymes. Gls and Gls2 isoforms are co-expressed in different brain regions and cells. Of note, location of Gls2-encoded isoforms in neuronal nuclei suggests a novel role in the regulation of gene expression. The co-expression of different GA isoforms in mammalian brain is so far unexplained. Our objective is to study the cerebral function of Gls2; for this purpose, we develop a conditional knockout (KO) mouse model to silence GAB and LGA expression in brain. A vector carrying the Gls2 gene from exon 1 to 12 (obtained from the EUCOMM consortium) was transfected by electroporation into B6D2F1 murine embryonic stem cells (ES). These ES were selected by geneticin and PCR-genotyped before their microinjection in 8-cell stage embryos (Swiss strain). Embryo implantation was performed in pseudopregnant state mice, which leads to chimeric pups. This vector targets chromosome 10 and will yield a conditional KO mouse model, since exons 2 to 7 are included between loxP sites. The chimeric pups carrying this modification within their germ line were used to generate the homozygous Gls2 (-/-) mice. After integration of the vector in both alleles, the mice will be mated with mutant Cre mice, which express this recombinase enzyme under control of the synapsin specific promoter. This will result in a deletion of the exons 2 to 7 giving rise to null Gls2 mutants mainly in the following brain areas: cortex, hippocampus, amygdala and cerebellum, which are essential for glutamatergic transmission and related to the mesolimbic pathway.
Keywords: Biología molecular; Bioquímica; Knockout Mice; Glutaminase; Gls2 gene